Will economic crisis happen? Мacroeconomic forecast for Russia 2007–2010 - Natalia Akindinova; Valery Mironov; Maxim Petronevich (Foresight and STI Governance)
Which scenario will be evolved in the Russian economy over the next three years? Will the investment activity and the level of consumer credit be sustainable? Will the ruble be strengthened, or his position once again will be shattered? These and many other questions are of constant worrying by the Russians. It is certain to say that virtually every major financial and economic developments in the country or the world is a cause for debate. It is known that the Russian government's medium-term forecast, covering the next decade, does not imply any defaults, but every crisis, and financial in particular, can become a cruel reality that violates all the plans.